OPTIMIZATION OF HYBRID POWER SYSTEM WITH PV PENETRATION : LOW, MEDIUM, AND HIGH FOR SENTANI SUBSTATION AND MERAH SUBSTATION (STUDY CASE JAYAPURA GRID) - Soadamara, Alamson
The current grid condition in Indonesia, which is highly dependent on thermal generation, produces high carbon emissions that can be harmful to humans and the environment. Much more friendly energy source solutions are already applied in the world. One of solution is hybrid power system. The Hybrid Power System is a combination of renewable energy sources with other backup sources, can be a diesel or a battery system storage. The example of the renewable energy that can be used is solar power. Solar PV has the highest resource potential in Indonesia at 532.6 GW, explained by the high solar resource across Indonesia. One area that has the potential as a solar energy source area besides NTB is Papua. The Papua Power System consists of several isolated electrical systems, one of which is the Jayapura Grid. Through a study of load flow analysis and optimal power flow, we can estimate the maximum capacity of hybrid power plant that can be penetrated On- Grid. The research was centered on two penetration points, namely in Sentani Substation and Merah Substation. With the distribution of penetration classes: low, medium and high, the best composition of the hybrid power plant can be determined based on the cheapest generating cost (BPP). After obtaining the capacity and composition to be applied, a power flow and transient analysis study must be carried out to determine the stability of the system, which are frequency and voltage stability.